2019
DOI: 10.1002/eco.2065
|View full text |Cite
|
Sign up to set email alerts
|

Landscape controls on the distribution and ecohydrology of central Oregon springs

Abstract: Small springs in semiarid landscapes are essential for maintaining aquatic biodiversity and supporting livestock grazing operations. However, little is known about controls on the distribution and physical characteristics of small springs, the aquatic species they support, or their sensitivity to disturbance. We address this information gap in the Crooked River subbasin, a tributary of the Deschutes River in Oregon. We conducted spatial analyses on 2,519 mapped springs to investigate the influence of landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…In general support of the structural geology approach, Naghibi and Dashtpagerdi (2017) found that the best predictors of the location of 842 springs in the Khalkhal region of Iran were altitude, topographic wetness index, slope angle, and faulty density. Freed et al (2019) reported that springs density in the Crooked River sub‐basin of the Deshutes River in Oregon was highest for springs discharging from low‐permeability rock units. However, description of springs in relation to landscape scale structural geology varies among physiographic provinces and does not distinguish individual springs.…”
Section: Springs Ecosystem Classification and Approachesmentioning
confidence: 99%
“…In general support of the structural geology approach, Naghibi and Dashtpagerdi (2017) found that the best predictors of the location of 842 springs in the Khalkhal region of Iran were altitude, topographic wetness index, slope angle, and faulty density. Freed et al (2019) reported that springs density in the Crooked River sub‐basin of the Deshutes River in Oregon was highest for springs discharging from low‐permeability rock units. However, description of springs in relation to landscape scale structural geology varies among physiographic provinces and does not distinguish individual springs.…”
Section: Springs Ecosystem Classification and Approachesmentioning
confidence: 99%
“…Reductions or changes in the volume or timing of groundwater discharge, whether from pumping or climate change, can affect GDEs in several ways. Changes in the amount and timing of groundwater discharge to lotic GDEs such as springs and rivers can lead to ecosystem drying, increased temperature and other water quality impairments, with direct impacts to GDEs (De Graaf et al, 2019; Eamus et al, 2015; Freed et al, 2019; Rohde et al, 2019). Within lentic GDEs such as fens and other groundwater‐fed wetlands, reductions in discharge or long late‐season recessions can lead to lowered water tables and organic soil oxidation, often leading to replacement of obligate groundwater‐dependent species with more generalist ones (Aldous & Bach, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This emphasis on the study and regulation of regional groundwater flow paths benefits our understanding of the ecohydrology of GDEs in low hypsographic positions. However, many small, low discharge, poorly studied GDEs are destroyed by dewatering of shallow local flow paths in ways that are not regulated and largely ignored by land and water managers (Freed et al, 2019; Sada et al, 2005; Sada & Vinyard, 2002). Conserving the full suite of biodiversity associated with groundwater discharge requires more focused attention on the smaller more local flow path associated GDEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, groundwater-dependent ecosystems are often associated with endemic and sensitive species with low resilience to impacts (Sada et al 2005;Kodric-Brown and Brown 2007;Freed et al 2019;Wolaver et al 2020). In arid regions in particular, such species may be found in only a few locations (Wolaver et al 2020).…”
Section: Challenges Of Managing Groundwater To Ensure Ecosystem Functionmentioning
confidence: 99%